PENGEMBANGAN MEDIA NEARPOD DALAM MODEL PBL UNTUK MATERI SUMBER DAYA ALAM KELAS V SD - Saifa Rizanna Aulia Alfath; Ninik Indawati; Triwahyudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of learning media that is not varied and interactive in elementary schools leads to low interest, focus, and engagement among students in the learning process. One digital learning medium that facilitates this process is Nearpod, and when used in conjunction with problem based learning (PBL), its usefulness increases. The purpose of this study is to develop Nearpod learning media for fifth grade elementary school students based on PBL (Problem-Based Learning) with content on natural resources, as well as to conduct feasibility and practicality tests. The ADDIE development model was used as the method. Data collection tools included questionnaires for teacher and student feedback, as well as validation from media, content, and language experts. Based on the research findings, the media validation scored 90%, content validation scored 97.5%, and language validation reached 92.85%. The research results indicate that the PBL based Nearpod media is highly feasible for use. As shown by the practical test results, which indicated a score of 99% from students and 97.91% from teachers, the PBL based Nearpod media is also considered highly practical. It is recommended that teachers continue to develop innovations in learning media, and further research can be conducted for comparison with other media in different learning contexts.